Rationalizing the Effect of the MAA/PEGMA Ratio of Comb‐Shape Copolymers Synthetized by Aqueous Free‐Radical Copolymerization in the Hydration Kinetics of Ordinary Portland Cements - Sara Beldarrain; Aitor Barquero; Guido Goracci; Jorge S. Dolado; Jose Ramon Leiza (Macromolecular Materials and Engineering, 2023)
Abstract Methacrylic acid‐co‐poly(ethylene glycol methacrylate) (MAA‐co‐PEGMA) copolymers (MPEG‐type polycarboxylate ether (PCE) superplasticizers) are characterized by a comb‐like structure. Although they have been used for years as dispersants in cementitious formulations, their structure–property relationship is still not fully understood. In this work, PCEs with uniform composition and different charge‐density (N) or different side chain lengths (P) are synthesized by free‐radical copolymerization varying the MAA/PEGMA ratios and ethylene oxide units in the PEGMA macromonomers. The effect of these copolymers on the hydration kinetics of an Ordinary Portland Cement (OPC) is analyzed, and it is observed that by increasing the PCE concentration the hydration is delayed. For a given PCE concentration, the delay is longer as the MAA/PEGMA ratio increases or the side chain length of the PEGMA decreases. The hydration delay is proportional to the carboxylate dosage and all PCEs fit in a master curve proving that the microstructure of the PCEs synthesized by free‐radical copolymerization can be correlated with the hydration delay of a commercial OPC.